Haematological effects of chronic benzene poisoning in 217 workers. Issue 3 (July 1971) - Aksoy, Muzaffer; Dinçol, Koray; Akgün, Turhan; Erdem, Şakir; Dinçol, Günçaǧ
Abstract : Aksoy, M., Dinçol, K., Akgün, T., Erdem, Ş and Dinçol, G. (1971). Brit. J. industr. Med., 28, 296-302. Haematological effects of chronic benzene poisoning in 217 workers. A haematological study consisting of the determination of RBC, WBC, PCV, platelets, and differential counts was carried out, together with bone marrow puncture and haemoglobin analyses in appropriate cases, on a control population of 100 normal people and on 217 male labourers, 95% of whom worked with solvents containing benzene in small shops manufacturing shoes under unhygienic conditions. The concentration of benzene in the workplaces ranged between 30 and 210 p.p.m., and the period of exposure between 3 months and 17 years. In 51 of the 217 workers (23·50%) haematological abnormalities attributable to chronic benzene poisoning were detected. Thus, leucopenia was present in 9·70%, thrombocytopenia in 1·84%, leucopenia associated with thrombocytopenia in 4·6%, pancytopenia in 2·76%, acquired pseudo-Pelger-Huet anomaly in 0·46%, lymphocytosis in 0·46%, giant platelets in 0·46%, eosinophilia in 2·30%, basophilia in 0·46%, and eosinophilia associated with basophilia in 0·46% (the maximum normal levels for eosinophils and basophils were 8% and 2% respectively). Acquired pseudo-Pelger-Huet anomaly was detected in a worker with heterozygous betathalassaemia (HbA2 4·1% and HbF 8·7%) in whom the only effect of benzene was on the leucocyte nuclei, all other haematological values being within normal limits. On the other hand, in 33·1% of the workers the haemoglobin was less than 12 g/100 ml and in 32·7% the PCV was less than 40% with the MCV ranging between 86 and 96 μm 3 . In none of them did MCV exceed 100 μm 3 . Thirty-one per cent. of these anaemic workers were treated with adequate doses of oral iron, which resulted, in all cases, in a complete disappearance of the anaemia. Therefore, it is difficult to attribute this anaemia to the effect of benzene alone. Thus it is concluded that benzene exerts its harmful effect, primarily on the leucocytes, with eosinophilia and basophilia as inconstant findings, secondarily on the platelets causing thrombocytopenia, and finally on all three series giving rise to pancytopenia.